2018
DOI: 10.1186/s12544-018-0311-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of urban public transport efficiency: case study of the Czech Republic

Abstract: The aim of this paper is to identify the factors influencing efficiency of urban public transport (UPT) systems and to benchmark Czech UPT systems according to their efficiency. Methods: The analysis was carried out on a sample of 19 UPT systems in the Czech Republic during 2010-2015. Efficiency was evaluated through a two-stage analysis. Data envelopment analysis (DEA) was used in the first stage. It was based on three inputs (employees, rolling stock and energy) and one output (passengers). DEA efficiency sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
3
19
1
2
Order By: Relevance
“…is result is inconsistent with the expectation and with the existing literature [3,12]. Population aggregation is the most direct reflection of urban attraction, competitiveness, and economic development.…”
Section: Influencing Analysis Of Exogenous Environment Factorscontrasting
confidence: 78%
See 3 more Smart Citations
“…is result is inconsistent with the expectation and with the existing literature [3,12]. Population aggregation is the most direct reflection of urban attraction, competitiveness, and economic development.…”
Section: Influencing Analysis Of Exogenous Environment Factorscontrasting
confidence: 78%
“…Public transport plays an important role in a city's sustainable development [2]. Consequently, public transport throughout the world is heavily subsidized by local governments [3]. In most countries, financial funds are strictly controlled.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…One of their main findings was that the efficiency of smaller transport systems which had a difficult access to funding sources was systematically less efficient. In other research, Fitzova et al (2018) identified factors influencing the efficiency of municipal public transport systems and compared Czech municipal public transport systems according to their efficiency. This analysis was performed on a sample of 19 systems in the Czech Republic for the period from 2010 to 2015.…”
Section: Introductionmentioning
confidence: 99%